Lepidoptera of tundra habitats of the northern Kola Peninsula, Northwestern Russia - Kozlov, Mikhail; Kullberg, Jaakko (Entomologica Fennica, 2008)
Sampling of 10 sites in 1994–2006 along roads connecting Murmansk with Teriberka and Dalniye Zelentsy yielded 140 species of moths and butterflies. Epinotia immundana and Ortholepis vacciniella are recorded for the first time from the Kola Peninsula, which increased the regional fauna to 690 species. Although some arcto-alpine species have been collected (in particular Sparganothis praecana, Catastia kistrandella, Euphydryas iduna, Glacies coracina), the fauna was clearly dominated by species typical for the forested habitats of the central part of the Kola Peninsula. This result suggests that the ‘routine’ sampling in north-eastern tundra between Murmansk and Ponoj might not be as important in terms of biogeography as it has been expected. Instead, new collecting trips should be oriented to areas with special vegetation, primarily limestone or sandy areas which are more likely to support more eastern and/or arctic species.